Incubation of social deficit during morphine abstinence in male mice using a novel unbiased and automatized method - Mathis, Victor P.; Giua, Gabriele; Torquet, Nicolas; Mittelhaeuser, Christophe; Bour, Raphael; Kieffer, Brigitte L.; Riet, Fabrice; Darcq, Emmanuel (Frontiers in Behavioral Neuroscience, 2025)
IntroductionOpioid use disorder (OUD) is a chronic relapsing condition caused by prolonged opioid exposure, which triggers adaptive changes in the brain. These changes make it challenging to control or abstain from consuming, and significantly increase the risk of relapse. While the physical symptoms of withdrawal typically resolve within a few days, extended abstinence is frequently accompanied by the progressive development of emotional disturbances. Additionally, abstinent individuals often report social disengagement, or even social isolation that worsen the condition and participates in the development of comorbidities. These disturbances are similarly observed in murine models of opioid abstinence.MethodsHowever, traditional methods for assessing social deficits in rodents often rely on simplistic paradigms with limited behavioral metrics. Here, we utilized a well-established model of morphine administration followed by protracted abstinence, combined with the Live Mouse Tracker (LMT) system. Using the real-time video-based automated LMT system, we conducted longitudinal recordings of social behaviors over a 4-week period of morphine abstinence, during repeated social interaction sessions.ResultsThe use of this method, offering an unbiased and precise behavioral characterization of social investigation between freely-moving male mice, revealed that while motor and activity-related disruptions emerge and resolve quickly immediately following the onset of abstinence, social deficits progressively intensify over time, reaching their peak 3 weeks after the final morphine administration. Additionally, the LMT provided detailed insights into subtle behavioral changes throughout the course of abstinence and within individual but also that early deficits in explorations and social interactions might serve as predictor for the severity of the late social deficits.DiscussionThese results point out the need to improve and implement unbiased tracking methods for a deeper and refined understanding of rodent behaviors modeling psychiatric conditions.